1984
DOI: 10.1115/1.3138471
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Human Tendon and Their Age Dependence

Abstract: There are no previously published data on changes in the mechanical behaviors of human tendon from maturation in the second decade to senectitude in the seventh decade or thereafter. In this study, 44 tendons from individuals ranging in age from 16 to 88 yr were subjected to an extensive series of mechanical tests which included preconditioning, extensions at strain rates of 100 percent/s, 1 percent/s, and 0.01 percent/s, and stress relaxation with cyclic and constant extensions. Pairs of extensions at 1 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
1
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(38 citation statements)
references
References 16 publications
4
30
1
1
Order By: Relevance
“…12,21,49,50 Our estimate, however, is higher than the average mechanical hysteresis value of ϳ10% reported from measurements on adult mammals. 5,25,45 This discrepancy may be accounted for, in part, by aging-induced increases in the mechanical hysteresis of tendon.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…12,21,49,50 Our estimate, however, is higher than the average mechanical hysteresis value of ϳ10% reported from measurements on adult mammals. 5,25,45 This discrepancy may be accounted for, in part, by aging-induced increases in the mechanical hysteresis of tendon.…”
Section: Discussioncontrasting
confidence: 70%
“…5,25,45 This discrepancy may be accounted for, in part, by aging-induced increases in the mechanical hysteresis of tendon. 21 Moreover, our in vivo method cannot exclude friction of the tendon and the patella as they pass over internal structures, such as the fat-pad lying posterior to the patella tendon. Internal friction is likely to oppose tendon recoil and result in overestimation of hysteresis as compared with in vitro conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In some studies it has been shown that the strain levels in#uenced the relaxation of the stress (Haut and Little, 1972;Lanir, 1980), while in other works, only slight strain dependence has been found for the relaxation modes (Hubbard and Soutas-Little, 1984;Soden and Kershaw, 1974). The necessary experiments have not yet been done for ligament tissues (Lakes and Vanderby, 1999).…”
Section: Introductionmentioning
confidence: 98%
“…One study suggests that aging produces stiffer and stronger tendons [50], but other investigations led to the opposite conclusion [44,54] or showed no effect of aging on most of the mechanical properties of the tendon [16]. In animals, tenocyte metabolism changes with increasing age [13], and these changes are accompanied by morphologic changes [6].…”
Section: Introductionmentioning
confidence: 99%